(untitled) (Research, Society and Development, 2022)
Removal of intraradicular retainers often becomes an obstacle when endodontic retreatment is required. The aim of this study was to describe an endodontic reintervention preceded by the removal of intraradicular posts using the Integrated Simultaneous Ultrasound System (SISU) technique. Female patient, feoderma, 34 years old, was referred for dental care at the Specialization Clinic in Endodontics, Faculdade São Leopoldo Mandic, Belo Horizonte Unit, with indication for endodontic reintervention of dental elements 14 and 15, both with the presence of intraradicular post. In the initial radiographic examination, it was possible to observe a slight thickening of the periodontal ligament in tooth 14 and the presence of a radiolucent image in the region adjacent to the root apex, suggestive of a periapical lesion in tooth 15. After confirming the need and feasibility of endodontic retreatment, removal was performed. of the prosthetic crown, followed by partial wear of the cast metal cores and removal of the cement line with a fine tip ultrasonic insert. After this procedure, two ultrasonic thick tip inserts were used, positioned simultaneously in opposite directions, so that the ultrasonic vibrations were transferred to the intraradicular retainers, thus allowing their removal. Endodontic retreatment was performed in two sessions, with intracanal medication for a period of 21 days. Patient under clinical and radiographic follow-up.